ANTESEDEN DAN KONSEKUENSI PENGGUNAAN MEDIA SOSIAL PADA PRODUK PRILAKU RAMAH LINGKUNGAN - Mohamad Faiq Ilmadina; Aftoni Sutanto; Purwoko Purwoko; Zunan Setiawan; Salamatun Asakdiyah (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study examines and analyzes the model of personality traits on social media activities, which can affect the environmentally friendly behavior of fashion production. The partial least squares structural equation modeling (PLS SEM) technique was used to evaluate the internal and external measurement models with a sample size of 272. The results revealed that the most active personality traits on social media were extraversion, openness to experience, and friendliness. In addition, the active use of social media has a positive impact on optimizing the user's environmentally friendly behavior and increasing user awareness of the product. This study combines the theory of personality traits and social media activity, to examine how consumers develop environmentally friendly behavior and environmental awareness in products.